Diretrizes de atendimento inicial ao paciente adulto queimado do Hospital Universitário de Maringá - Pedro, Cavalari Junior (2023)
Burns are traumatic injuries and can be caused by various etiological agents, being classified as 1st, 2nd and 3rd degree, affecting the epidermis, dermis and hypodermis, respectively. With the burn, the skin loses its function of thermal regulation, protection against environmental agents, and blood flow control. Our objective was to develop a flowchart for the initial care of adult burn patients at the Maringá University Hospital. For this, an integrative literature review was conducted from 2012 to 2022, with a qualitative approach of full articles English, Portuguese and Spanish available in the SciELO (Scientific Eletronic Library Online), PubMed/Medline (Online System for Search and Analysis of Medical Literature), LILACS (Latin American and Caribbean Literature on Health Sciences), CAPES Periodical Portal databases. As descriptors were used the terms: Guidelines (Guideline); Burns (Burn); Emergency (emergency); Burn Units (Burn Units). Exclusion criteria were patients aged <18 years, burns in the eyes, and articles with low evidence. This review identified 211 studies, 13 of which were selected by separating duplicates and reading the title and abstract. Of these, 8/13 described about the types of cleaning and dressings used in dressings, 5/13 articles recommended the Advanced Trauma Life Support (ATLS) principles for initial anamnesis, 6/13 used the Parkland formula for volume replacement, 3/13 indicated the tetanus vaccine and the application of heparin as prevention. Regarding analgesia, 5/13 articles suggest the use of intravenous opioids and, as an alternative, nonpharmacological treatments. With the perspective of improving and standardizing care, 2/13 describe the importance of training the multidisciplinary team involved in assisting the burn patient. It is concluded then that there are few studies that describe the first care of the burned patient and it is necessary to develop a flowchart for the standardization of care, especially in the emergency room of the University Hospital of Maringá.